Global trends and research hotspots in perioperative management of lung cancer: a bibliometric analysis from 2004 to 2024 - Jiang, Qinling; Wei, Zhuheng; Liu, Pingping; Li, Zonghuai; Jiang, Huiqin; Cao, Yilin; Zhang, Bo; Yan, Yuanyuan; He, Yulong (Frontiers in Immunology, 2024)
ObjectiveThis article aims to analyze the current status and research hotspots of literature related to perioperative management of patients with Lung Cancer and provide reference for future research directions.MethodsThis study conducted a bibliometric analysis of research literature related to perioperative management of Lung Cancer published between 2004 and 2024, retrieved from the Web of Science database. R software and VOSviewer were used for analyzing keyword clusters and research themes, revealing trends and frontiers in this field.ResultsA total of 4,942 studies on perioperative management of lung cancer were included. In recent years, research in this area has shown a global upward trend, with particular focus on surgical risk assessment, complication prevention, and postoperative management. Perioperative biomarkers before and after surgery have emerged as a central focus due to their impact on diagnosis and treatment. The application of novel therapies, such as targeted drugs and immunotherapy, in perioperative management is also becoming a significant research hotspot. Additionally, China has been a leading contributor to research output in this field, demonstrating strong performance in international collaborations.ConclusionPerioperative management is a critical factor influencing the prognosis of Resectable lung cancer patients. Through a systematic analysis of the current status and research hotspots in perioperative management of lung cancer, this study provides valuable references for future clinical practice and research, particularly regarding the integration of novel therapies to optimize patient outcomes.